Comparative study of organic and conventional vegetable farming systems using material and substance flow analysis / Leong Hong Yeng - Leong, Hong Yeng (2016)
Increase in human population has led to increased demand for food production. Thus, it is essential to adopt sustainable agricultural development. Organic farming is generally seen as a sustainable agriculture practice with lower environmental impact however, the low yield is unable to meet the food demand. High production conventional agriculture is often associated with significant environmental impact. This has raised the debate on sustainability issues of organic and conventional production. This study investigates two organic (OF) and two conventional vegetable farms (CF) to assess the sustainability and efficiency of each farm with material and substance flow analysis (MFA and SFA) using STAN 2.5 software. Based on STAN model, the annual C balance were around 6,315 ± 2,529, 9,912 ± 1,816, -304 ± 12,988 and 10,802 ± 4,929 kg C ha-1 y-1 in CF1, CF2, OF1 and OF2, respectively. The C balance of CF1, CF2 and OF2 are classified as ―sink‖ while OF1 stock change is classified as ―source‖. The C flow highlights that major C input was from photosynthesis that contributed about 3,803 ± 2,123, 358 ± 40, 1,193 ± 506, 3,944 ± 3,107 kg C ha-1 y-1 of C flux in CF1, CF2, OF1 and OF2, respectively. The N balance of all the study farms were categorized as N ―sink‖ given the N balances of 1,589 ± 116, 1,605 ± 8, 2,608 ± 18, and 912 ± 220 kg N ha−1 year−1 in CF1, CF2, OF1, and OF2, respectively. The primary N input at OF1 and OF2 was compost, which accounts for 81% (2,201 kg N ha−1 year−1) and 60% (815 kg N ha−1 year−1) of the total N input. Chemical fertilizer used at CF1 and CF2 were about 1,334 and 941 kg N ha−1 y−1 while chicken manure contributed 343 and 572 kg N ha−1 y−1, respectively. This study concludes farm level management plays an important role in achieving sustainable agriculture. The study demonstrates MFA and SFA with STAN software allow a comprehensive assessment of agri-indicators from different views and aspects.